The role of vitamin D and UVB on the risk and survival of oesophageal and gastric cancer - O' SULLIVAN, FIONA (Trinity College Dublin. School of Medicine. Discipline of Public Health & Primary Care, 2018)
The Role of Vitamin D and UVB on the Risk and Survival of Oesophageal and Gastric Cancer By Fiona O?Sullivan Background: Vitamin D is a fat-soluble vitamin which has many sources. Currently, there are numerous ways in which vitamin D can be measured or estimated, such as 25-hydroxyvitamin D (25(OH)D) measurement, UV dose estimation or dietary estimates from food or sun exposure questionnaires. Each of these methods have limitations associated with them and it is difficult to determine which estimate gives the best assessment of a person?s vitamin D status. In recent years there has been a resurgence in vitamin D research using each of these methods. Many studies carried out have found a beneficial effect of vitamin D on the risk and survival of many diseases and conditions, such as osteoporosis, cardiovascular diseases and cancer. There has been some strong evidence supporting an inverse association between vitamin D and the risk and survival of various cancers, such as prostate, breast and colorectal cancers. However, the relationship between vitamin D and oesophageal and gastric cancer occurrence and mortality has been mixed. Aim: The overall aim of this study was to develop a simple method of using ambient UVB measurements, along with personal characteristics to predict average vitamin D status of individuals. Utilisation of this method alone and along with 25(OH)D measurements where available, was used to investigate the effect of vitamin D, on the risk and survival of oesophageal and gastric cancer. Methods: Numerous cohorts were used in this study, including; a cohort of 92 Crohn?s patients from St James?s Hospital, the ?Trinity, Ulster and Department of Agriculture Cohort? (n=5,138), the ?UK Biobank Cohort? (n=500,000) and the ?Irish Gastric and Oesophageal Cancer Biobank Cohort? (n=265). UVB doses over Ireland and the UK were explored using UVB data from the ?Tropospheric Emissions Monitoring Internet Service? database. A number of estimates of vitamin D were created in this thesis; individually calculated cumulative and weighted UVB dose (cw-D-UVB), annual UVB, and a vitamin D scoring system which contained detailed UVB data along supplementation use, oily fish consumption and time spent outdoors. Associations between UVB, the created vitamin D scores and 25(OH)D concentrations were examined using regression methods. Random forest analysis and receiver operating curves were used in the classification of individuals into vitamin D deficient and sufficient categories. Conditional logistic regression was used to determine associations between UVB, vitamin D scores and the risk of oesophageal or gastric cancer occurrence. Cox-proportional hazard ratios and Kaplan-Meier curves were used to examine the association between UVB, vitamin D scores, 25(OH)D and the survival of oesophageal and gastric cancer in two different cancer cohorts. Results: In this thesis, wide variations in D-UVB dose in Ireland and the UK were observed between seasons, latitudes and longitudes despite the small latitude and longitude differential within these countries. This has important implications for future UV and vitamin D estimations. Strong associations between 25(OH)D concentration, cw-D-UVB dose and vitamin D scores in two Irish cohorts were also determined. These estimates (cw-D-UVB dose and vitamin D scores) were also found to be important for the prediction of 25(OH)D deficiency and sufficiency in a cohort of older participants. A reduced odds of oesophageal and gastric cancer occurrence was observed when comparing higher tertiles with lower tertiles for both annual D-UVB and vitamin D scores. A reduced risk of gastric cancer morality was also observed when comparing tertile 2 with tertile 1 of vitamin D scores and 25(OH)D in two different cohorts. This trend was also noted using annual D-UVB in an Irish cohort. No consistent associations were found for any upper gastrointestinal cancer or oesophageal cancer mortality. Conclusion: This thesis demonstrates the importance of accurate and detailed measurement of UVB exposure not only when describing differences in UVB doses between countries but also when investigating the relationship between UVB (as estimation of vitamin D) and health outcomes. This research also demonstrates the beneficial impact of higher levels of various vitamin D estimates in the risk of upper gastrointestinal cancers. As all estimates of vitamin D are found to have certain flaws, further research is needed in a larger cohort of individuals using multiple estimates of vitamin D such as; annual D-UVB, vitamin D scores and 25(OH)D concentrations, in order to fully explore the relationship between vitamin D and the risk and survival of oesophageal and gastric cancers.
APPROVED
Keywords: Vitamin D; UVB; Oesophageal cancer; Gastric cancer